Informatics as a particular field of education - Szlávi, Péter; Zsakó, László (Teaching Mathematics and Computer Science, 2005)
Informatics education can be discussed at various levels. There is informatics education at the university, there is professional informatics training and there is public informatics education. In the following article we are going to deal with the latter, that is we are going to discuss what areas of informatics should be introduced to students within the frame of the informatics subject in primary and secondary education.Knowledge in connection with informatics can be grouped from different points of view. We consider the following points to be acceptable: according to scopes of knowledge. [1, 2]